Investigating the Dimension of Applying the Accounting Standard-Borrowing Costs-on International Monetary Fund (IMF) Loans by Purchasing Management - Amal Noori Mohammed (International Journal of Supply Chain Management, 2019)
Abstract-The discussion of the international standards in general, and the international accountingstandards in particular are admittedly recognized as messing with de facto truths. Purchasing management for trading with the IMF is an essential issue which should be considered in the organization structure. This research has aimed to draw the attention of the Commission of international Accounting standards to a simple part within the international Accounting standard which is (borrowing costs). The fact that this criterion settled for identifying the practical steps in the description of the accounting treatment through the capitalization of borrowing costs and did not mention the accounting treatment for loans costs' that may be endured by the lender when the borrower fails to repay part or all of the loaned amount. As this part were not discussed under any item of the standard items, when there is doubt or failure of the borrower to pay the value of the debt (loan), and for the goal of protecting the lender on one hand and to integrate Accounting Standard - loan costs-on the other, therefore this study concludedthe necessity of pointing out to adding a part to that standard or devoting a separate item for that topic (Inability to repay the loaned amount wholly or partially by the borrower). As this research presented how to handle this case from an accounting point of view, and also this research suggesting changing the name of that standard from Borrowing costs to loans costs, giving a wider meaning to the parties to the loan lender and the borrower.